SLIPT-Assisted Dual-Hop VLC/RF With Relay Selection: Outage Probability Analysis and Optimization - Khoe Ta, van; Hong, Ic-Pyo; Tran, Giang N. (IEEE access, 2025)
This paper proposes a hybrid visible light communication/radio frequency (VLC/RF) system with simultaneous lightwave information and power transfer (SLIPT) utilizing relay selection to take the advantages of both VLC and RF systems in terms of spectrum efficiency and coverage. The relay is selected from multiple devices in the VLC coverage and equipped with both solar cell and RF antenna for energy harvesting, receiving signal and transmitting message to the end user. Especially, the devices in optical communication range are randomly located with the uniform distribution, and the light intensity from the light emitting diode (LED) contains alternating current (AC) and direct current (DC) elements for the signal detection and energy harvesting. The relay decodes the signal to retransmit to the end user by harvested power via RF channels in the second hop. Then, we derive the closed-form of the outage probability (OP) of the proposed system. The analytical expression of the OP performance is validated by simulation results, and the impacts of parameters of the system are examined. The results show that the increase in the number of the relay can reduce the OP and transmitted power. The high value of threshold of transmission rate at the relay can increase the error in the performance. In addition, decreasing AC value and boosting DC value can enhance OP performance of the system, and vice versa. Moreover, the optimization problem is formulated to minimize the OP performance subject to AC peak value and DC bias to satisfy linear characteristics of the LED operation. To solve the optimization problem, the particle swarm optimization (PSO) algorithm is deployed and modified to attain the optimal solution. The PSO algorithm greatly improves the OP performance in comparison to the numerical method.